Comparison of physical workload and physical work capacity among municipality cleaners in Shiraz to determine number of workers needed to counterbalance physical workload - Farnaz Bagherifard; Hadi Daneshmandi; Mansour Ziaei; Haleh Ghaem; Ruhollah Khoshbakht; Omid Jaberi; Alireza Choobineh (BMC, 2022)
Abstract Background Assessing physical workload is the most important step in deciding whether a workload is high and adopting appropriate control strategies to reduce physical workload. This study aimed to compare physical workload and Physical Work Capacity (PWC) among municipality cleaners in Shiraz to determine the number of workers needed to counterbalance physical workload. Methods The present cross-sectional study was performed on 97 municipality cleaners in Shiraz. In the first step, the participants' maximum aerobic capacity (VO2-max) was estimated in the laboratory using an ergometer bicycle and the Young Men's Christian Association (YMCA) protocol, based on which the PWC was estimated. Secondly, energy expenditure and heart rate during work were measured using a POLAR400 device in an eight-hour shift. At the end of the work shift, the workers' perceived physical exertion was assessed using a Rating of Perceived Exertion 6-20 (RPE 6-20) Borg scale. In the final stage, the physical workload was assessed based on the results of the two steps. Results The mean VO2-max of the cleaners and PWC were estimated to be 2.6 ± 0.66 l min−1 and 4.3 ± 1.088 kcal min−1, respectively. The average energy consumed during work was 4.122 ± 1.016 kcal min−1. The overall results of this study showed that physical workload was greater than PWC in 46% of the municipality cleaners. In addition, it was found that 12.45% workforce was required to be added to the street cleaners of Shiraz municipality to reduce the physiological workload on the employed workforce. Conclusions With respect to the high level of physical activity in a significant proportion of the cleaners, measures such as increasing the workforce are suggested.